Aktualisasi Diri Tokoh Utama dalam Novel Mimpi, Cinta, dan Inspirasi Karya Gloria Morgen - Erina Dwi Ajeng Umorowati; Fitriyana Puspitaningsih; Eva Dwi Kurniawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aims to to determine the actualization needs of the main character Kate in the novel Mimpi, Cinta, dan Inspirasi using the humanistic psychological theory of the hierarchy of needs by Abraham Maslow. The material object used is a story about the process of actualization needs from restless to fulfilled. The method used uses qualitative descriptive methods. Descriptive method is a research method aimed at describing existing phenomena that take place now or in the past. The findings of this study are in the physiological needs needed by characters in the form of mimuman. In the need for security, in the form of the need for a sense of security, stability, dependence, protection, freedom from fear, anxiety and confusion. The needs of love include the need for love, affection and friendship. The need for self-esteem is gaining recognition. The need for self-actualization shows that the main character has found his identity. The main character Kate has achieved self-actualization after going through life's journey through a hierarchy of needs.